On the Crank-Nicolson difference scheme for the time-dependent source identification problem - Ashyralyev, A.; Urun, M. (KU Publ., 2021)
In this study the source identification problem for the one-dimensional Schr¨odinger equation with non-local boundary conditions is considered. A second order of accuracy Crank-Nicolson difference scheme for the numerical solution of the differential problem is presented. Stability estimates are proved for the solution of this difference scheme. Numerical results are given.
Дереккөзді идентификациялау бейстанционарлы есебі үшін Кранк-Николсонның айырымдық схемасы туралы
О разностной схеме Кранка-Николсона для нестационарной задачи идентификации источника
Keywords: identification problem; Schr¨odinger equation; difference scheme; Crank-Nicolson; stability